Meat quality of lambs fed different saltbush hay (Atriplex nummularia) levels - Moreno, Greicy M. B. (2015)
Climate changes have increased soil and water salinity, compromising animal production especially in dry areas where scientists have become more interested in halophyte plants, like saltbush. The effects of saltbush hay levels (30, 40, 50 and 60%) were evaluated based on physical-chemical, nutritional and sensory parameters of Santa Ines lamb meat. Thirty-two 8-month-old castrated Santa Ines lambs, with initial weights of 22 +/- 1.97 kg were used; they were slaughtered after 60 days in the feedlot. The pH, colour, moisture, protein and cholesterol contents did not differ among treatments. Panelists observed a greater intensity of lamb smell and flavour (P=0.0035) in the meat of animals that received more concentrate in the diet. An increase in the inclusion of saltbush increased ash percentage (P=0.0232), total saturated (P=0.0035) and polyunsaturated (P=0.0287) fatty acids and reduced the lipids (P=0.0055) and the n-6: n-3 ratio (P=0.0058) of the meat. Therefore, saltbush hay can be used as a feeding resource in regions with problems of water and soil salinity because it does not impair the physical-chemical, nutritional and sensory quality of sheep meat.